GAMBARAN ONSET ANALGETIK KETOROLAC DAN SKALA NYERI PADA PASIEN POST SECTIO CAESAREA DENGAN SPINAL ANESTESI DI RSUD BAUBAU SULAWESI TENGGARA - Fadil, Fadil; Rahmanaya,; Ikit Netra W, (Jurnal Cakrawala Ilmiah, 2023)
Postoperative cesarean section pain experienced by a mother due to result in an incision in the abdominal wall or uterus. One way to relieve pain is to give the analgesic ketorolac. Research aims for knowing description ketorolac to loss effect analgesics and pain levels in post secti caesarea patients at the Palagimata Baubau Hospital, Southeast Sulawesi. This research method is descriptive observational with purposive sampling technique . The number of samples in this study amounted to 30 postoperative patients. Data were taken directly from the subject as a source of information under study, namely the results of observations of post sectio caesarea patients . The results showed that 20 respondents (66.7%) were in the 5-6 hour category and 10 respondents (33.3%) were in the 3-4 hour category. A total of 11 respondents (36.7%) had a mild pain scale, 10 respondents (33.3%) had scale painful which Heavy and 9 respondent (30.0%) have scale painful which is being. To the Palagimata Baubau Hospital, especially for the anesthesiologist, they continue to give the analgesic ketorolac and other combinations of analgesics to postoperative secti patients. caesarea.